Analisis Buku "Pathway to English" Untuk Kelas 11 berdasarkan Silabus pada Kurikulum 2013 - Niken Noputri; Ridho Kurniawan; Diana Oktavia; Yahfenel Evi Fussalam (Jurnal Muara Pendidikan, 2021)
This research was conducted to find out whether the “Pathway to English” textbook of the 11th grade used by SMAN 1 Bungo fulfilled syllabus points at the first semester in the 2013 curriculum and how extras the textbook presented. The result showed that Pathway to English textbook fulfilled 12 of 16 items of basic competence and 5 from 6 items of learning material in syllabus points. 12 basic competences were provided in some exercises of 4 English skills. The learning materials were successfully developed and supported with materials about social function formed cooperating tasks, text structures were available and related the other rules of text structures, and also language features. However, this textbook had weakness about there were none available BC 3.3 (Analyzing the social functions, the structure and language features of expressing hopes, according to the contexts), BC 4.3 (Constructing spoken and written text to express hopes, according to its social functions, structure and language features), BC 4.5 (Editing formal invitation letter according to its social functions structure and language features) and BC 4.6 (Writing formal invitations, according to its social functions, structure and language features).